ANALISIS FAKTOR KINERJA KARYAWAN JASA PENILAI PUBLIK MUTTAQIN BAMBANG PURWANTO ROZAK USWATUN DAN REKAN PALEMBANG - Trihandayani, Zaleha; Cahyani, Eni; Fitriah, Wani; Lina, Debbi Augus (Universitas Muhammadiyah Palembang, 2024)
Purpose– This study aims to knowing analyzing the factors that influence employee performanceDesign/methodology– The type of research used in this study is associative research. The population of all permanent employees of the Public Appraisal Service Office (KJPP) MBPRU Palembang Branch totaling 163 employees, obtained the number of samples using the Slovin formula, namely 70 employees with a 1% error rate. The sections include Property Appraisers, Marketing, Administration and Engineering & Administration.The data used are primary data and secondary data, Operational performance variables are measured by Quantity of Work Results, Quality of Work Results and Work Discipline, Competence is measured by Knowledge, Understanding and Ability (skill), Work discipline variables are measured Effective use of time, Complying with all organizational or company regulations and Work Targets and Organizational culture variables are measured by Innovation and success in taking risks, Attention to detail and results-oriented. Data collection used in this study were interviews, questionnaires and documentation. Data analysis using the SPSS program and data analysis techniques were carried out by instrument testing and multiple linear regression analysis, hypothesis testing and coefficient of determination.Findings - The results of the study together There is a significant influence of competence, discipline and organizational culture on the performance of employees of the Public Appraisal Service Office (KJPP) MBPRU Palembang Branch. There is a significant influence of competence on the performance of employees. There is a significant influence of discipline on the performance of employees. There is a significant influence of organizational culture on the performance of employees.